Are root cause analyses recommendations effective and sustainable? An observational study. (16th January 2018) - Hibbert, Peter D; Thomas, Matthew J W; Deakin, Anita; Runciman, William B; Braithwaite, Jeffrey; Lomax, Stephanie; Prescott, Jonathan; Gorrie, Glenda; Szczygielski, Amy; Surwald, Tanja; Fraser, Catherine
Abstract: Objective: To assess the strength of root cause analysis (RCA) recommendations and their perceived levels of effectiveness and sustainability. Design: All RCAs related to sentinel events (SEs) undertaken between the years 2010 and 2015 in the public health system in Victoria, Australia were analysed. The type and strength of each recommendation in the RCA reports were coded by an expert patient safety classifier using the US Department of Veteran Affairs type and strength criteria. Participants and setting: Thirty-six public health services. Main outcome measure(s): The proportion of RCA recommendations which were classified as 'strong' (more likely to be effective and sustainable), 'medium' (possibly effective and sustainable) or 'weak' (less likely to be effective and sustainable). Results: There were 227 RCAs in the period of study. In these RCAs, 1137 recommendations were made. Of these 8% were 'strong', 44% 'medium' and 48% were 'weak'. In 31 RCAs, or nearly 15%, only weak recommendations were made. In 24 (11%) RCAs five or more weak recommendations were made. In 165 (72%) RCAs no strong recommendations were made. The most frequent recommendation types were reviewing or enhancing a policy/guideline/documentation, and training and education. Conclusions: Only a small proportion of recommendations arising from RCAs in Victoria are 'strong'. This suggests that insights from the majority of RCAs are not likely to inform practice or process improvements. Suggested improvements include more human factors expertise and independence in investigations, more extensive application of existing tools that assist teams to prioritize recommendations that are likely to be effective, and greater use of observational and simulation techniques to understand the underlying systems factors. Time spent in repeatedly investigating similar incidents may be better spent aggregating and thematically analysing existing sources of information about patient safety.